Tinjauan Viktimologi Kekerasan dalam Rumah Tangga terhadap Anak di Desa Ciruas Pasar - Nabila Raihana; Neng Rahayu; Reggina Lhutfia Wardah; Widya Rahmawati Asmara; Intan Salsabila Fahmika; Mariatul Adawiyah Sopandi; Annisa Fazriani (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
In the perspective of victimology, children who are victims of domestic violence are viewed as a vulnerable group that needs protection and justice. This study aims to analyze the patterns of victimization, factors, and legal protection for child victims of Domestic Violence in Ciruas Pasar Village. The research method used in this study is empirical juridical. The data sources consist of primary and secondary data collected using interview techniques and field studies, and analyzed using qualitative descriptive methods. The results of this study indicate that children as victims of Domestic Violence experience complex victimization, including physical and verbal violence perpetrated by the father figure with a background of economic problems and emotional instability. The lack of public awareness, the victims' courage to report, and limited access to rehabilitation services are factors contributing to the inadequate implementation of legal protection for child victims of Domestic Violence in Ciruas Pasar Village. Therefore, synergy between the government, law enforcement agencies, social institutions, and the community is needed to create a more effective, inclusive, and sustainable child protection system.